Театральне мистецтво на західно-українських землях у 1918–1939 роках - Боньковська, О. (Студії мистецтвознавчі, 2007)
The author analyses the most characterizing trends in the Ukrainian dramatic art in 1918-1939, specific features of production of G. Yura's, O. Zagarov's, Y. Stadnyk's, V. Blavatskyy's and plays of other Ukrainian playwrights.